Stok Karbon Organik Sedimen di Kawasan Ekosistem Mangrove Pesisir Kabupaten Kolaka Sulawesi Tenggara: Organic Carbon Stock in the Mangrove Ecosystem Area of Kolaka Coastal Line Southeast Sulawesi - Fajar Hasidu; Maharani Maharani; Gaby Nanda Kharisma; Ramlah Saleh; Putri Grace Simamora; Sri Rezeki; Arif Prasetya; La Ode Muhamad Hazairin Nadia; Zulfathri Randhi; Hasan Eldin Adimu (Jurnal Sumberdaya Hayati, 2023)
Mangrove ecosystem can absorb and store carbon stock in their biomass and sediment. This ecosystem plays an important role in the carbon cycle. This study aimed to analyze the C-organic content and organic carbon stock of sediment, also CO2 absorption. The sediment sampling was conducted in the Kolaka Coastal line mangroves using a Peat Auger for 1 m of sediment depth. Then the sediment was separated into four layers. Then the sediment samples were oven dried at 50°C for 1 week for sediment bulk density analysis (SBD). The analysis of the C-organic content of sediment was done by the LOI method. The estimation of sediment carbon stock using sediment C-organic data and SBD data. The results showed that the highest average of C-organic content was in station 3 (4.12±0.15%). In the othher hand, the highest average of SBD was in station 1 (0.67±0.02 g cm-3). Overall, the total of sediment C-organic stock in station 1 was higher than other station (233.67±11.90 Mg C ha-1). The total capacity of CO2 absorption by sediment in the station 1 was also higher than other station (856.77±37.66 Mg CO2 ha-1). The sediment C-organic stock was influenced by C-organic content and SBD value.